Duality Centre - Suburbs: Origins by the Re-use of Religious Buildings - Virtudes, Ana L. (2020)
The nationalization of religious properties; churches, convents and monasteries, signifying the decline and the end of the religious orders and a selling-off (by auction) of their properties was a universal phenomenon that took place in several countries in different times. In Portugal, this process occurred in 1834 and has contributed greatly to urban transformations. The changing of European cities in the transition to the twenty century has some aspects in common, such as is the resultant transformation of the compact urban fabric to a city with the duality between centre and suburbs, but there are others which are unique and Santarém is one such case. This uniqueness lies not in the result but in the cause of the change: this process means the re-using, transforming and rebuilding of religious spaces and their functions in order to meet new demands for the city. If on the one hand a bullfighting arena, some military buildings or even a prison were the new facilities of the suburbs, a theatre, an archaeological museum, a bank agency, a high school or a housing area for the bourgeoisie on the other hand were to become the new architecture of the city centre in the religious spaces. All the examples mentioned above were to lead to the adjustment of city limits. The city limits ceased to be identified in relation to the city-walls and the concept of a new city was formed by an internal dualism between city centre and suburbs. This process made the example of this city unique and caused a series of unique urban changes. During this peculiar socio-political process in Santarém, the new commercial bourgeoisie arose and its strong desire for land-ownership and buying-up the religious spaces. There were a large number of convents and their location was both inside and outside the city-walls. The city geography was this: it lay on a platform on top of the hill above the Tagus River and this brought in turn some unexpected beauty and quality to the urban design. The transformation of religious spaces was a key factor in urban design. This change occurred within the context of a bourgeoisie in full social ascent, who had their own ambitions for the city. Consequently, the city was fragmented into different spatial areas having different social characters: the city centre was beautiful, regular, healthy and desirable; the suburbs were irregular, unhealthy and a bidonville for citizens with little means.